Zastosowanie wybranych metod statystycznych w badaniach marki - Kozłowski, Artur; Olszewska, Małgorzata (The Usage of Selected Statistical Methods in Brand Analysis, 2005)
The authors of the following paper made a survey on the product of a brand in the sample representing its custommers. On the basis of collected data brand identification was estimated and custommers satisfaction analysis of the purchase was carried out. The analysis was conducted by means of logit models, multiple choice models and discrimination analysis. Presented methods may be used by firms to make a diagnosis of factors influencing products' regarding of the examined brand. Applications of these methods enables to select these factors that are crucial for strengthening the brand in the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 444-452